Pembelajaran Fisika Berbasis Kompetensi Life Skill Kelas XII IPA.1 MAN 1 Lampung Selatan - Poniman, Poniman (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2016)
This study aims to determine the physics competency-based learning life skills class XII IPA1, It conducted in two cycles, each cycle consisting of four phases: planning, execution, analysis and reflection. The action used is "Competency-Based Physics Education Life Skills". The first cycle has not succeeded cognitive aspects obtained a mean value of 5.62, the affective with good criterion 32.35%, sufficient criteria 67.65% as well as psychomotor  with good criterion 38.34%, sufficient criteria 61.66%, the life skill with all criteria 41.18%, both criteria 58.82 %.The second trying to provide intensive training with the same material, the result of learning on the cognitive of  a mean value of 5.81, affective  with both criteria of 76.47%, sufficient criteria 23.53%, psychomotor with good criterion 55.88%, sufficient criteria of 44.12% as well as on the life skill with very good criteria 1.76%.Penelitian ini bertujuan untuk mengetahui dampak pembelajaran fisika berbasis kompetensi life skill pada kelas XII IPA1. Penelitian ini dilakukan dalam dua siklus, setiap siklus terdiri dari empat tahap: perencanaan, pelaksanaan, analisis dan refleksi. Tindakan yang digunakan adalah "Pembelajaran Fisika Berbasis Kompetensi Life Skills ". Siklus pertama belum berhasil, nilai rata-rata aspek kognitif diperoleh 5,62; afektif dengan kriteria baik 32,35%, dan kriteria cukup 67,65%; serta psikomotorik dengan kriteria baik 38,34%, dan kriteria cukup 61.66%; life skills dengan semua kriteria 41,18%, kriteria baik 58,82%. siklus kedua mencoba untuk memberikan pelatihan intensif dengan tindakan yang sama, rata-rata hasil belajar aspek kognitif 5,81; afektif dengan kriteria baik 76,47%, kriteria cukup 23,53%, psikomotor dengan kriteria baik 55,88%, kriteria cukup 44,12% serta pada life skill dengan kriteria baik sekali 1,76%.